Kajian Persepsi Dan Sikap Petani Dalam Pengembangan Sistem Pemasaran Kontrak di Gapoktan Tani Makmur Kelurahan Lingkar Selatan Kecamatan Paal Merah Kota Jambi - Nida Kemala; Tengku Yaasir Alhafizh (Jurnal MeA (Media Agribisnis), 2023)
This research was conducted in the Lingkar Selatan Sub-District, Paal Merah District, Jambi City. Some of the objectives in this study were to describe the contract marketing system, perceptions and attitudes of farmers towards the contract marketing system, and to analyze the relationship  between perceptions and attitudes of farmers towards the contract marketing system at Farmer group ”Tani Makmur”. Collected 47 farmers as a samples from 87 populations was taken by proportional random sampling method. To see the relationship between perceptions and attitudes, the Chi Square test was used. The results showed that in  this farmer group,  there was still only one farmer group that implemented this contract marketing system, namely Rizqy's group. This system had been going on since November 2020. The mechanism for determining the agreement was carried out by 2 parties, namely farmers and food entrepreneurs. This agreement concerns to the type of commodity (lettuce), the duration of the contract, the quantity of requested product supply, the price and the transaction system. 35 farmers (74.48%) have a positive perception and 12 farmers (24.54%) farmers have a negative perception toward to this contract marketing system. Based on attitude, there were 32 farmers (68.08%) who had a supportive attitude and 15 farmers (31.92%) who did not support the contract marketing system. The results of the statistical analysis showed that there was a strong relationship between perceptions and attitudes of farmers towards to the contract marketing system.